2021
DOI: 10.1177/2325967121992133
|View full text |Cite
|
Sign up to set email alerts
|

The Area of Impingement in the Throwing Versus Nonthrowing Shoulder of Collegiate Baseball Players: An MRI Study of the Simulated Late-Cocking Phase of Throwing

Abstract: Background: During shoulder abduction and external rotation, internal impingement can occur when compressive forces between the greater tuberosity and the posterior glenoid rim pinch the undersurface of the rotator cuff. Previous studies on internal impingement have focused on qualitative results such as pathological findings; however, few studies have quantified the area of impingement (AOI) of the rotator cuff muscles between the greater tuberosity and the posterior glenoid rim. Purpose: To compare the AOI b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…From the results of this study, the PGHD was associated with AOI, which re ected the rotator cuff tendons existing between the greater tuberosity and posterior glenoid rim. Takahashi et al [15] reported that the AOI of the throwing shoulder with morphologic change in the posterior glenoid rim was higher than that of the non-throwing shoulder, indicating an increase in the area of the rotator cuff tendons between the humeral head and posterior glenoid rim. Morphologic changes in the posterior glenoid rim diminish the bumper effect of the posterior glenoid rim and impair its protective role as a "wall."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the results of this study, the PGHD was associated with AOI, which re ected the rotator cuff tendons existing between the greater tuberosity and posterior glenoid rim. Takahashi et al [15] reported that the AOI of the throwing shoulder with morphologic change in the posterior glenoid rim was higher than that of the non-throwing shoulder, indicating an increase in the area of the rotator cuff tendons between the humeral head and posterior glenoid rim. Morphologic changes in the posterior glenoid rim diminish the bumper effect of the posterior glenoid rim and impair its protective role as a "wall."…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on internal impingement, which is a phenomenon wherein the undersurface of the rotator cuff tendons is pinched between the greater tuberosity and posterior glenoid rim during shoulder abduction and external rotation of the late cocking phase [6]. Internal impingement syndrome is frequently observed in baseball players and is associated with throwing shoulder injuries, such as rotator cuff injury, labrum injury, and humeral head cysts [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shoulder health and pathology in the overhead athlete remains a particularly important topic of scholarship today. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, in this issue, we feel very fortunate to publish the very latest:…”
mentioning
confidence: 99%